Development of a Health Information Technology Tool for Behavior Change to Address Obesity and Prevent Chronic Disease Among Adolescents: Designing for Dissemination and Sustainment Using the ORBIT Model - Kepper, Maura M.; Walsh-Bailey, Callie; Brownson, Ross C.; Kwan, Bethany M.; Morrato, Elaine H.; Garbutt, Jane; de las Fuentes, Lisa; Glasgow, Russell E.; Lopetegui, Marcelo A.; Foraker, Randi (Frontiers in Digital Health, 2021)
Health information technology (HIT) has not been broadly adopted for use in outpatient healthcare settings to effectively address obesity in youth, especially among disadvantaged populations that face greater barriers to good health. A well-designed HIT tool can deliver behavior change recommendations and provide community resources to address this gap, and the Obesity-Related Behavioral Intervention Trials (ORBIT) model can guide its development and refinement. This article reports the application of the ORBIT model to: 1) describe the characteristics and design of a novel HIT tool (the PREVENT tool) using behavioral theory; 2) illustrate the use of stakeholder-centered “designing for dissemination and sustainability” principles; and 3) discuss the practical implications and directions for future research. Two types of stakeholder engagement (customer discovery and user-testing) were conducted with end-users (outpatient healthcare teams). Customer discovery interviews (n=20) informed PREVENT tool components and intervention targets by identifying: 1) what healthcare teams (e.g., physicians, dietitians) identified as their most important “jobs to be done” in helping adolescents who are overweight/obese adopt healthy behaviors; 2) their most critical “pains” and “gains” related to overweight/obesity treatment; and 3) how they define success compared to competing alternatives. Interviews revealed the need for a tool to help healthcare teams efficiently deliver tailored, evidence-based behavior change recommendations, motivate patients, and follow-up with patients within the constraints of clinic schedules and workflows. The PREVENT tool was developed to meet these needs. It facilitates prevention discussions, delivers tailored, evidence-based recommendations for physical activity and food intake, includes an interactive map of community resources to support behavior change, and automates patient-follow-up. Based on Self Determination Theory, the PREVENT tool engages the patient to encourage competence and autonomy to motivate behavior change. The use of this intentional, user-centered design process should increase the likelihood of the intended outcomes (e.g., behaviour change, weight stabilization/loss) and ultimately increase uptake, implementation success, and long-term results. After initial tool development, user-testing interviews (n=13) were conducted using a think-aloud protocol that provided insight into users’ (i.e., healthcare teams) cognitive processes, attitudes, and challenges when using the tool. Overall, the PREVENT tool was perceived to be useful, well-organized, and visually appealing.